Rancang Bangun Sistem Informasi Sekolah Berbasis Web Untuk Komunikasi Antara Guru Dan Orang Tua Murid Di SDN Harapan Jaya II Bekasi Menggunakan Metode String Matching - Chuzaimi, Ahmad; Basry, Asril (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
In the current era of rapid scientific and technological progress, information plays animportant role in driving progress in various fields. Information technology and computersplay an important role in facilitating human work and in solving various problems. Thisresearch aims to design and build a web-based school information system that facilitatescommunication between teachers and parents at SDN Harapan Jaya II Bekasi. This systemwas developed using the String Matching method to increase efficiency in searching anddelivering information. With this system, it is hoped that communication between teachersand parents will be more effective and structured, and can support the overall teaching andlearning process. The research results show that the system developed is able to meet thecommunication and information needs of the school well.